(3caGjI GdeJMaX hfgGjI GdeJdaXs - (3CHh ESMGb Hf EHQGgje Hf ESeGYjd Hf CMeO, GdCLOGHj GdWQGHdSj s ((3MdH s)
(3ChdgG (B:s
(3bGd GdTjN GdGLOGHi GdMeO ddg QH GdYGdejf gPG cJGH eNJUQ ai GddZI heG jMJGL EdgjG ef ZQjH GdcdGe s
(3BNQgG (B:s
(3hGdOHGdI GdaJjdI , hLeYgG PHGd hgj GdTYjdI CjVkG hLeYgG TYGFjd hGddg CYde HNRJ caGjI GdeJMaX s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG bQGAI SfI (B614s
(3jhLO GjVG JMJ Qbe (B2885 s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GddZIs